Інституційно-зумовлені причини та передумови формування урядів меншості у європейських парламентських демократіях - Панчак-Бялоблоцька, Надія (Lviv Politechnic Publіshing House, 2016)
Проаналізовано інституційно-зумовлені причини і передумови формування урядів меншості у європейських парламентських демократіях. Виявлено, що інституційна зумовленість урядів меншості у парламентських демократіях є доволі різносторонньою, але переважно окреслюється проблематикою політичної стабільності та політичної культури. The article is dedicated to analysing institution-based reasons and background of minority governments’ formation in the European parliamentary democracies. The researcher has found that the institutional conditionality of minority governments in parliamentary democracies is quite versatile, but is mostly defined with problems of political stability and political culture. The study showed that clarification of the political and institutional based characteristics, nature, causes and features of government formation and functioning in the European parliamentary democracies has both ideological and conceptual meaning, because it can testify on the generalized specifics of governments at all and can show the patterns of parliamentary democracies functioning in the cases of parliamentary minorities. This is particularly noteworthy in the view of the fact that minority governments are not unified and monolithic structures in the context of the European institutional practices. The fact is that they differ in their composition, dimensionality, ideologies, reasons of formation and peculiarities of responsibility. That is why different types of minority governments in the European parliamentary democracies are able to produce various political, legal and socio-economic impacts and to be determined by different formative and functional parameters. In addition, determining specifics of minority governments is essential in view of the fact that these institutional structures of cabinets account for more than thirty percent of all European (in Western, Central and Eastern European countries) governments, thus, minority government, as the European experience and comparative statistics show, is a "normal" phenomenon of political process and inter-institutional relations in parliamentary democracies. Accordingly, the elucidation of their institution-based reasons of formation is important theoretically, methodologically and empirically.
Institution-based reasons and background of minority governments’ forming in the european parliamentary democracies
Keywords: уряд; уряд меншості; причини та передумови формування урядів меншості; парламентська демократія; інститути; політична стабільність; Європа; government; minority government; the causes and conditions of minority governments’ formation; parliamentary democracy; institutions; political stability; Europe